2013
DOI: 10.1155/2013/296727
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of the Biological Effects of Carbon Nanotube-Coated Dental Zirconia

Abstract: The purpose of this study is to evaluate functionalized multiwalled carbon nanotubes (fMWCNTs) as a potential coating material for dental zirconia from a biological perspective: its effect on cell proliferation, viability, morphology, and the attachment of an osteoblast-like cell. Osteoblast-like (Saos-2) cells were seeded on uncoated and fMWCNT-coated zirconia discs and in culture dishes that served as controls. The seeding density was 104 cells/cm2, and the cells were cultured for 6 days. Cell viability, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The a-C:H:N coated Y-TZP surfaces revealed a low adhesion of bacteria on the surface compared to uncoated surfaces [83]. Other studies have also coated zirconia with functionalized multiwalled carbon nano-tubes increasing the roughness, wettability, and cell adhesion of this material favoring zirconia´s osseintegration properties [90,91].…”
Section: Laranjeira Et Al Compared the In Vitro Behavior Of Fibroblamentioning
confidence: 97%
“…The a-C:H:N coated Y-TZP surfaces revealed a low adhesion of bacteria on the surface compared to uncoated surfaces [83]. Other studies have also coated zirconia with functionalized multiwalled carbon nano-tubes increasing the roughness, wettability, and cell adhesion of this material favoring zirconia´s osseintegration properties [90,91].…”
Section: Laranjeira Et Al Compared the In Vitro Behavior Of Fibroblamentioning
confidence: 97%
“…Nanotubes can induce inflammatory and fibrotic reactions under some conditions by crossing membrane barriers. [98][99][100][101][102] Graphene Teeth coating, suitable for implantation, biofilm reduction Cost effectiveness, fracture resistant, low density form a uniform crystal lattice, treat bacterial biofilm…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Applications of CNTs, which may allow ingestion, are steadily increasing, and can include their implementation as adsorbents in water purification systems [141], or as antimicrobial agents or stabilizing materials in food packaging [142]. Recently, Prajapati et al [143] investigated the use of CNTs as carriers for orally administered anti-parasite treatment in rats, with possible application in humans, and Kou et al [144] identified functionalized MWCNTs as a promising coating material of dental implants for better osseointegration [144]. There have been observations that residual hydrophobic compounds, which are often adsorbed to CNTs during their synthesis, were released more rapidly in the presence of gastric enzymes and increased salt concentration in simulated GI fluids.…”
Section: Other Routes Of Exposure-gastrointestinal Tractmentioning
confidence: 99%